2014
DOI: 10.1021/ie5024645
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Water Vapor Adsorption on Single-Layer Molecular Sieve 3A: Experiments and Modeling

Abstract: The objective of the current work was to shorten the gap for fundamental adsorption kinetic data required for the development of advanced adsorption unit-operation models to be incorporated into an overall plant-level model for spent nuclear fuel reprocessing. The kinetics of water-vapor adsorption on molecular sieve 3A was investigated at 25–80 °C and water dew points from −69 to 17 °C. Water uptake curves were fitted with three kinetic models including the linear-driving-force model, the shrinking-core model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…Previous studies have shown that silver ions inside the mordenite crystals were reduced to metallic silver and formed silver nanoparticles on the surface of the crystals during the reduction by hydrogen . Physical properties and chemical characteristics of the MS3A and Ag 0 Z were described previously . In addition to those reported properties, the average macropore radii of MS3A and Ag 0 Z were measured in this work using mercury porosimetry, which were 35 nm and 26.5 nm, respectively.…”
Section: Kinetic Adsorption Data Acquisitionmentioning
confidence: 61%
See 4 more Smart Citations
“…Previous studies have shown that silver ions inside the mordenite crystals were reduced to metallic silver and formed silver nanoparticles on the surface of the crystals during the reduction by hydrogen . Physical properties and chemical characteristics of the MS3A and Ag 0 Z were described previously . In addition to those reported properties, the average macropore radii of MS3A and Ag 0 Z were measured in this work using mercury porosimetry, which were 35 nm and 26.5 nm, respectively.…”
Section: Kinetic Adsorption Data Acquisitionmentioning
confidence: 61%
“…Both solid adsorbents were microporous crystalline alumina silicates that have micropores and channels in the crystals. The commercial MS3A that were used in prior studies were spherical beads with a radius of 1.18 mm, and the Ag 0 Z used in prior studies were extruded cylinders with a radius of 0.8 mm.…”
Section: Kinetic Adsorption Data Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations